Peluang dan Tantangan Produk Asuransi Syariah Berbasis Wakaf dalam Meningkatkan Perlindungan Sosial - Purwanto, Andi; Mugiyati (Mukaddimah: Jurnal Studi Islam, 2025)
Sharia insurance is one of the sharia financial instruments that functions as social protection for the community. However, the development of sharia insurance is still not optimal, especially in terms of the products and services offered. Waqf is one of the sharia financial instruments that can be used as a basis for developing innovative sharia insurance products. This study aims to identify opportunities and challenges in developing innovations in sharia insurance products based on waqf, as well as to find out how innovations in sharia insurance products based on waqf can improve social protection for the community. The results of the study indicate that there are several opportunities and challenges in developing innovations in sharia insurance products based on waqf, including low public awareness, lack of professional human resources, and ignorance about general sharia insurance products. However, with the innovation of sharia insurance products based on waqf, it is hoped that it can improve social protection for the community and increase public awareness of the importance of social protection.